Heat flow and vertical groundwater flux in deep fractured basement rock in Nara Basin, southwest Japan - Pathak, Dinesh (Journal of Nepal Geological Society, 2003)
The temperature measurement in a borehole that intersects the flow zone is one of the effective methods to detect the vertical flow of water. Geothermal gradients, thermal conductivity, and heat flow have been assessed for the crystalline basement and the overlying sedimentary cover in the study area. The geothermal gradient in sedimentary cover ranges from 0.83-3.87 °C/100 m, whereas in the basement rock it ranges from 2.49-3.38 °C/100 m. The heat flow values in sedimentary cover and basement rocks lies between 13.46 and 56.87, and 79.89 and 108.63 mW/m2, respectively. Vertical specific discharge of groundwater flow in the fractured basement rock is estimated for different depth intervals. Groundwater in the unconsolidated sediment and at most places in fractured rocks is moving vertically down. However, at some locations, water is moving upward especially at greater depth intervals. The calculated vertical specific discharges reflect the relative degree of fracturing in the basement rocks at the corresponding depth intervals.